1999
DOI: 10.1037/1076-8998.4.4.337
|View full text |Cite
|
Sign up to set email alerts
|

The source, nature, and direction of work and family conflict: A longitudinal investigation.

Abstract: The authors examine the source, nature, and direction of work and family conflict. Confirmatory factor analysis of a 22-item scale suggested the appropriateness of distinguishing between strain-based and time-based conflict and between family interfering with work (FIW) and work interfering with family (WIF). Six-month longitudinal survey data (N = 236) suggested that strain-based FIW is a precursor to both stress and turnover intentions. Strain-based WIF emerged as an outcome of stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
400
0
28

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 516 publications
(445 citation statements)
references
References 17 publications
17
400
0
28
Order By: Relevance
“…The measure of a student's intention to drop out is based on the prior research by Meyer and colleagues (Meyer, Allen, & Smith, 1993) and Kelloway and colleagues (Kelloway, Gottlieb, & Barham, 1999) where the level of commitment was found in both studies to determine the level of turnover. As with prior research, commitment was shown to significantly impact turnover intention, with higher commitment being associated with lower turnover intention and, importantly, lower likelihood of actually dropping out.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The measure of a student's intention to drop out is based on the prior research by Meyer and colleagues (Meyer, Allen, & Smith, 1993) and Kelloway and colleagues (Kelloway, Gottlieb, & Barham, 1999) where the level of commitment was found in both studies to determine the level of turnover. As with prior research, commitment was shown to significantly impact turnover intention, with higher commitment being associated with lower turnover intention and, importantly, lower likelihood of actually dropping out.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Meyer, Allen, and Smith (1993) studied the dropout intention of nursing students and found that the level of commitment determined the level of turnover. Similarly, Kelloway, Gottlieb, and Barham (1999) studied employees that may or may not be experiencing work-family conflict and again found that the level of commitment determined the level of turnover. Given these findings and the predictions offered in Bean's model, we offer the following hypothesis related to turnover intention:…”
Section: Turnover Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…timebased WIF, strain-based WIF, time-based FIW, and strain-based FIW), which has not been properly considered previously. However, as there were differences in the present sample compared to that reported by Kelloway et al (1999), a factor-analysis was carried out to check for differences in the underlying factor structure. The present analysis was only able to identify between WIF and FIW conflicts, not between the strain-based and time-based conflicts.…”
Section: Methodsmentioning
confidence: 99%
“…Work-family conflict was assessed by the 22-item workfamily conflict scale developed by Kelloway et al (1999). The scale distinguishes between WIF and FIW conflicts and between strain-and time-based conflicts (while time-based conflict is experienced when time pressures associated with one role prevent one from fulfilling the expectations of the other role, strainbased conflict is experienced when strain or fatigue in one role affects performance in the other).…”
Section: Methodsmentioning
confidence: 99%